Investigating the Assembly Status of the Plastid Encoded Polymerase Using BN-PAGE and Sucrose Gradient Centrifugation - Jeannette Pfalz (Bio-Protocol, 2016)
The plastid encoded polymerase (PEP) represents a major transcription machinery in mature chloroplasts (Liere et al., 2011; Zhelyazkova et al., 2012). The proper assembly of this multi-subunit complex is important for plant growth and development (Pfalz and Pfannschmidt, 2013). The PEP polymerase can be purified from soluble and from membrane-bound (also named transcriptionally active chromosome, TAC) fractions. Blue Native polyacrylamide gel electrophoresis (BN-PAGE) and sucrose gradient sedimentation followed by immunoblot analyses is used to detect the status of the PEP complex assembly.